Near-shore current observations in the Gulf of Cadiz - Laiz, Irene; Navarro, Gabriel; Rodríguez-Gálvez, Susana; Pelegrí, Josep Lluís; Ruiz Segura, Javier (2007)
I Interntarional Symposium in Marine Sciences (ISMS07), Simposio GLOBER - IMBER España (2007), celebrado del 28 al 31 de marzo de 2007 en Valencia.-- 1 page Most studies of the surface circulation of the Gulf of Cadiz have used either remotely sensed sea-surface temperature (SST) or climatological data. However, a considerable effort has recently been made in order to study both its northern (Criado-Aldeanueva et al., 2006; García-Lafuente et al., 2006; Ruiz and Navarro, 2006; etc) and southern portions (Machín et al., 2006) from in situ data. García-Lafuente et al. (2006) describe a cyclonic circulation cell between Cape Santa Maria and Guadalquivir River that characterises the spring-summer season. García-Lafuente and Ruiz (2006) hypothesises that this cyclonic cell breaks during winter, giving rise to the characteristic anticyclonic circulation that one would expect according to the North Atlantic Subtropical Gyre eastern boundary current system. On the other hand, the surface circulation in the Gulf of Cadiz is subject to short-term variability following the change in the wind regime from westerlies to easterlies. [.] Peer reviewed